Analisis Jarak Microphone Array dengan Teknik Pemrosesan Sinyal Fast Fourier Transform Beamforming - Moh. Fausi; Agus Naba; Djoko Santjojo (Fakultas Teknik, Universitas Brawijaya, 2015)
The main problem in the application of the sound source detection is to estimate the angle of the wave or called as Direction Of Arrival (DOA) of Planewave. The method commonly to overcome the problem to utilize the sensor array by the data processing technique such as a beamforming technique. In this research was done by DOA estimation that used technique Fast Fourier Trasnfrom (FFT) beamformer with sensor configuration by Uniform Linear Array (ULA). The analysis has been to determine the distance of the array microphone that has DOA estimation with high accuration to the real source posisition. Based on the variation of distance of array microphone tested, shown the 6 cm is the bes distance which has the most dominant DOA estimation results with high accuracyKeywords : DOA , FFT Beamforming , Array sensor , ULA